2016
DOI: 10.1063/1.4967992
|View full text |Cite
|
Sign up to set email alerts
|

The effect of thermal treatment on the stress state and evolving microstructure of Cu/W nano-multilayers

Abstract: The functionality and reliability of nano-multilayered devices and components are largely affected by the stress evolution during fabrication, processing, and operation. The impact of thermal treatment on the stress state and evolving microstructure of Cu/W nano-multilayers, as deposited on different substrates (i.e., Si(001), Al 2 O 3-C, and Al 2 O 3-R) by magnetron sputtering, was investigated by in-situ high temperature X-ray diffraction and high-resolution scanning electron microcopy. The as-deposited Cu a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 55 publications
2
33
0
Order By: Relevance
“…Annealing up to 500 ºC fully releases the stresses of the Cu nanolayers [19], which also coincides with the temperature at which a high number of Cu protrusions appear on the surface [18]. At T > 700 ºC, degradation of the NML structure occurs [18,19]. Consequently, it is suggested for W 25nm + (Cu 5nm /W 5nm ) × 100 that upon heating (> 500 ºC) Cu penetrates through the W layers to the bond interface.…”
Section: Methodsmentioning
confidence: 60%
See 2 more Smart Citations
“…Annealing up to 500 ºC fully releases the stresses of the Cu nanolayers [19], which also coincides with the temperature at which a high number of Cu protrusions appear on the surface [18]. At T > 700 ºC, degradation of the NML structure occurs [18,19]. Consequently, it is suggested for W 25nm + (Cu 5nm /W 5nm ) × 100 that upon heating (> 500 ºC) Cu penetrates through the W layers to the bond interface.…”
Section: Methodsmentioning
confidence: 60%
“…As shown by these studies, in the as deposited state very high compressive stresses (related mainly to growth stresses initiate by the PVD process) were observed in the confined Cu (≈ -1.5 GPa) and W layers (≈ -3.5 GPa) [19]. Annealing up to 500 ºC fully releases the stresses of the Cu nanolayers [19], which also coincides with the temperature at which a high number of Cu protrusions appear on the surface [18]. At T > 700 ºC, degradation of the NML structure occurs [18,19].…”
Section: Methodsmentioning
confidence: 67%
See 1 more Smart Citation
“…Various kinetic models have been proposed to describe the stress generation mechanisms during the different stages of thin-film growth, for example, due to island nucleation and growth, due to island coalescence and grain boundary formation ('zipping'), and due to the incorporation of adatoms into grain boundaries during the post-coalescence growth stage (Chason et al, 2012). The growth stresses in functional thin films and multilayers affect their thermal (Moszner et al, 2016;Druzhinin et al, 2019;Cancellieri et al, 2016), chemical (Delph & Jaccodine, 1999) and mechanical properties (Streitz et al, 1994;Wen et al, 2007). Hence fundamental knowledge on stress generating and relaxation mechanisms in thin films and multilayers is needed to tune their functional properties.…”
Section: Introductionmentioning
confidence: 99%
“…The study of its thermal behaviour revealed the degradation of the multilayer structure, transforming into a spheroidised nanocomposite at 700°C [29]. The migration of Cu to the surface of the multilayer and the feasibility of joint formation was attributed to the relaxation of the compression stresses accumulated in each layer mainly during the deposition process [30].…”
Section: Introductionmentioning
confidence: 99%